PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU EKSTRA PERAN (OCB) MELALUI KOMITMEN ORGANISASIONAL KARYAWAN RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Apriliani Hardiyanti (Master of Management, Mataram University, 2016)
This study aims to analyze the effect of Organizational Culture and Transformational LeadershipStyle Role Of Conduct Extras (OCB) Through Employee Organizational Commitment RegionalGeneral Hospital City Mataram. The population in this study are employees (doctors, nurses,midwives), which amounted to 246 employees with a sampling technique that Proportionate RandomSampling was 71 employees. This type of research is the study associative causality. Data collectiontool is a questionnaire containing questions about the variables Organizational Culture,Transformational Leadership Style, Behavior Role Extras (OCB) and Organizational Commitment.Data analysis was performed with Path Analysis Model Triming using SPSS AMOS. The analysisfinds that organizational culture positive and significant effect on the behavior of extra role (OCB).Organizational culture positive and significant effect on organizational commitment.Transformational leadership style and no significant positive effect on the extra role behavior (OCB).Transformational leadership style positive and significant effect on organizational commitment.Work motivation positive and significant effect on organizational commitment. Organizationalcommitment and significant positive effect on Extra Role Behavior (OCB). Organizational Cultureand Transformational Leadership Style positive and significant impact on Extra Role Behavior(OCB) Through Employee Organizational Commitment Regional General Hospital City Mataram.Keywords: Organizational Culture, Transformational Leadership Style,Behavior Role Extras (OCB), and Organizational Commitment.